Constant time horizon prediction-based control for linear systems with time-varying input delay. Issue 2 (2020) - Kong, SiJia; Bresch-Pietri, Delphine
Abstract: We introduce a constant time horizon prediction-based controller to compensate for a time-varying input delay in a linear control system. We establish that this controller guarantees closed-loop exponential stability, provided that the time-varying delay remains sufficiently close to its average value D0 and its rate of variation sufficiently small. This conclution only has to hold in average, in a mathematical sense that we specify.